Customary and Islamic Law in the Piduduk Tradition of Banjar Weddings in Perbaungan - M Qodri Salam; Irwan (Universitas Ibn Khaldun, 2026)
The Piduduk tradition in Banjar weddings remains a subject of debate because it represents customary heritage, while some of its earlier practices may conflict with the Islamic principle of monotheism. This study analyzes the interaction between customary law and Islamic law in the implementation and reinterpretation of Piduduk and examines the role of community leaders in preserving the tradition in Perbaungan District, Serdang Bedagai Regency. This empirical legal research employed a qualitative approach and a single-site case-study design. Primary data were collected through semi-structured interviews conducted on 21–25 September 2025 with a customary leader, a religious leader, and a community member, and were supplemented by direct observation of the tradition’s material preparation. Secondary data were obtained from scholarly literature and the 2024 profile document of Cinta Tanah Air Village. The data were analyzed through reduction, data display, conclusion drawing, and verification, while their credibility was established through source and technique triangulation. Because the study relies on three informants at a single research site, its findings are presented as an in-depth illustrative account rather than a representative description of Banjar communities in general. Within these boundaries, the findings demonstrate that customary and Islamic law interact through conflict, accommodation, and integration. Piduduk has gradually been reinterpreted by these informants from a practice associated with offerings and supernatural protection into a cultural symbol of prayer, gratitude, marital advice, sharing sustenance, and social solidarity. Under Islamic law, Piduduk constitutes ’urf fasid when it involves belief in powers other than Allah, but it may be accepted as ’urf shahih when its mystical elements are removed. Customary and religious leaders play complementary roles in preserving Banjar identity while directing the tradition toward Islamic principles. Keywords: Banjar community; customary law; Islamic law; Piduduk tradition; ’urf